The effects of cell density and intrinsic porosity on structural properties and adsorption kinetics in 3D-printed zeolite monoliths. (8th June 2020) - Lawson, Shane; Adebayo, Busuyi; Robinson, Chad; Al-Naddaf, Qasim; Rownaghi, Ali A.; Rezaei, Fateme
Graphical abstract: Highlights: Fabrication of 3D-printed monoliths with different wall porosity and cell density. Evaluation of monoliths' dynamic CO2 /N2 separation performance at varied conditions. Faster CO2 mass transfer rate over monoliths made from a macroporous binder. Reduced CO2 mass transfer rate over monoliths with increased cell density. Abstract: Herein, we report the evaluation of dynamic performance of 3D-printed zeolite monoliths for CO2 /N2 separation at 5 bar 25 °C. Monoliths with various cell densities (200, 400, 600 cpsi) and porosities (0.23–0.46) were printed and the effects of cell density, wall porosity, and inlet gas velocity on their separation performance were investigated. Dynamic breakthrough tests with 10% CO2 /N2 revealed that increasing cell density gives rise to gas throttling, inadequate time for molecular mass transfer, and broad wavefronts. For 200 cpsi monoliths, upon increasing wall porosity from 0.23 to 0.46, the mass transfer zone (MTZ) length decreased from 0.40 cm to 0.07 cm at the feed velocity of 1.8 cm/s. The mass transfer coefficients estimated from modeling the breakthrough profiles were found to decrease steadily with both velocity and monolith cell density. In the macroporous samples, the best mass transfer coefficient was found to be 0.049 s −1 for the 200 cpsi monolith with kaolin binder substitution. Both increasing the plasticizer concentration and substituting a macroporous binder promoted mass transfer rate, however, the former method increased the number of zeolite-bentonite bonds around large surface defects during burnout and reduced the CO2 adsorption capacity by 27% from the other formulations. On the basis of adsorption capacity and kinetics, utilization of a macroporous binder was found to be the best method of developing 3D-printed zeolite monoliths because it could reduce intraparticle resistance without compromising adsorption capacity or mechanical integrity.